Peningkatan status gizi balita melalui pemberian daun Kelor(moringa oleifera l.) pada masa pandemi Covid19 - Indah Sari; Linawati Novikasari; Setiawati Setiawati (Holistik Jurnal Kesehatan, 2023)
Background: Data shows that more than half of cases of malnutrition status in the world occurs in Southeast Asia, which is as much as 27.6% or 5.2 million. Based on data from Basic Health Research in 2018 stated the prevalence of malnutrition and malnutrition in toddlers, as many as 3.9% of toddlers with malnutrition and 13.8% undernourished. The prevalence of underweight and very thin toddlers in Lampung Province based in 2018 is 11.8%. According to the Strategic Plan of the West Lampung District Health Office 2017-2022 the percentage of achievement is 1.41%.Purpose: To find out the improvement of the nutritional status of toddlers through the consumption of moringa leaves (Moringa oleifera L.) during the covid19 pandemic.Method: This type of research is Quasi Experiment (pseudo-experimental design) with one group pretest and posttest design. The population in this study was all toddlers who experienced undernutrition status in Suka Jaya Village and the sample was a population that met the inclusion criteria of 20 people.Results: The analysis there is effect of moringa leaves(Moringa oleifera L.)on the increase in nutritional status of children aged 4-5 years before and after the intervention is carried out statistical tests, namely the T-Test One Sample Test. Statistical test results showed the value of p-value = 0.000 (p<0.05) after the intervention of the nutritional status of children increased by 0.9.Conclusion: From the results of the study concluded that it was obtained an increase in nutritional status with the provision of moringa leaves (Moringa oleifera L.).Keywords: Nutritional Status; Moringa Leaves; Toddlers; Covid19 PandemicPendahuluan: Data menunjukkan bahwa lebih dari setengah kasus status gizi kurang di dunia terjadi di Asia Tenggara yaitu sebanyak 27,6% atau 5,2 juta. Berdasarkan data Riset Kesehatan Dasar (Riskesdas) tahun 2018 menyatakan prevalensi gizi buruk dan gizi kurang pada Balita, sebanyak 3,9% balita dengan gizi buruk dan 13,8% gizi kurang. Prevalensi balita kurus dan sangat kurus di Provinsi Lampung berdasarkan Riskesdas 2018 adalah 11,8% . Menurut Rencana Strategis (RENSTRA) Dinas Kesehatan Kabupaten Lampung Barat 2017-2022 presentase capaian adalah sebesar 1,41%.Tujuan: Untuk mengetahui peningkatan status gizi balita melalui pemberian daun kelor (Moringa Oleifera L.) pada masa pandemi covid19.Metode :Jenis penelitian ini adalah Kuasi Eksperimen (rancangan eksperimen semu) dengan desain One Group Pretest and Posttest. Populasinya seluruh ibu dan balita yang mengalami status gizi kurang di Desa Suka Jaya dan sampelnya yang memenuhi kriteria inklusi yaitu sebanyak 20 partisipan.Hasil: Ada pengaruh pemberian daun kelor (Moringa Oleifera L.) terhadap kenaikan status gizi anak usia 4-5 tahun sebelum dan sesudah intervensi dilakukan uji statistik yaitu Uji T-Test One Sample Test. Hasil uji statistik menunjukan nilai p value = 0.000 (p<0.05) setelah dilakukan intervensi status gizi anak mengalami kenaikan 0.9.Simpulan: Didapatkan peningkatan status gizi dengan pemberian daun kelor (Moringa Oleifera L.).